Revisiting the evolution of Ostrinia moths with phylogenomics (Pyraloidea: Crambidae: Pyraustinae). (13th September 2021) - Yang, Zhaofu; Plotkin, David; Landry, Jean‐François; Storer, Caroline; Kawahara, Akito Y.
Abstract: Reconstructing a robust phylogenetic framework is key to understanding the ecology and evolution of many economically important taxa. The crambid moth genus Ostrinia contains multiple agricultural pests, and its classification and phylogeny has remained controversial because of the paucity of characters and the lack of clear morphological boundaries for its species. To address these issues, we inferred a molecular phylogeny of Ostrinia using a phylogenomic dataset containing 498 loci and 115 197 nucleotide sites and examined whether traditional morphological characters corroborate our molecular results. Our results strongly support the monophyly of one of the Ostrinia species groups but surprisingly do not support the monophyly of the other two. Based on the extensive morphological examination and broadly representative taxon sampling of the phylogenomic analyses, we propose a revised classification of the genus, defined by three species groups ( Ostrinia nubilalis species group, Ostrinia obumbratalis species group, and Ostrinia penitalis species group), which differs from the traditional classification of Mutuura & Munroe (1970). Morphological and molecular evidence reveal the presence of a new North American species, Ostrinia multispinosa Yang sp.n., closely related to O . obumbratalis . Our analyses indicate that the Ostrinia ancestral larval host preference was for dicots, and that O . nubilalis (European corn borer) and Ostrinia furnacalis (Asian corn borer) independently evolved a preference for feeding on monocots (i.e., maize). Males of a few Ostrinia species have enlarged, grooved midtibiae with brush organs that are known to attract females to increase mating success during courtship, which may represent a derived condition. Our study provides a strong evolutionary framework for this agriculturally important insect lineage. Abstract : Classification of the moth genus Ostrinia is revised using a phylogenomic dataset, thus providing a strong evolutionary framework for this agriculturally important insect lineage. Morphological and molecular evidence reveal the presence of a new North American species, Ostrinia multispinosa Yang, that is closely related to the smartweed borer Ostrinia obumbratalis . Larvae of the ancestral Ostrinia likely preferred feeding on dicots, but two species, European corn borer and Asian corn borer, each independently evolved a preference for feeding on monocots.